Occupational therapy in rheumatoid arthritis: short term prospective study in patients treated with anti-TNF-alpha drugs - M. Gentili; M. Di Franco; V. Riccieri; L. Magrini; R. Scrivo; F. Ceccarelli; L. Mastrodonato; F. Pasqui; G. Valesini; A. Spadaro (PAGEPress Publications, 2011)
Objective: to assess the effect of occupational therapy (OT) in rheumatoid arthritis (RA) patients treated with anti- TNF-alpha drugs in a short-term open controlled prospective study. Methods: 31 RA subjects [(M/F=5/26; mean age= 56 (range=28-73) years; mean disease duration= 165 (range =15- 432) months], treated with anti- TNF-alpha drugs, were allocated to OT (n=15) or control (n=16) group. We evaluated at entry and 12 weeks the following outcome parameters including Health Assessment Questionnaire (HAQ), Short-Form Health Survey (SF-36), Global Health (GH), Ritchie index, number of swollen or tender joints, pain, patient and physician disease activity, Disease Activity Score (DAS28), erythrocyte sedimentation rate (ESR), C-reactive protein CRP) and the correct adherence to items regarding activity daily living (ADL). Results: at baseline, OT and control group had similar demographic and clinical features. After 12 weeks, the changes from baseline of main outcome parameters were not significantly different between the two groups. After 12 weeks, in 7 out of 11 items regarding ADL, the percentage of patients showing a correct adherence was significantly increased in OT group only. Moreover at the end of the study, the OT group showed a correct adherence to 8 out of 11 ADL items in an higher percentage of patients respect to the control group. Conclusion: our study sustains that OT improves self-management but not main parameters of disease activity or functional capacity. Nevertheless educational intervention should be considered as a useful tool in conjunction with pharmacological treatment.